Mechanical Efficiency in Chronic Obstructive Pulmonary Disease. Issue 2 (March 2017) - Gosens, Willem; van't Hul, Alex J.; Oomen, Joost M.; Hesselink, Matthijs K. C.; Borghouts, Lars B.
Abstract : PURPOSE: The primary aims of this study were (1) to evaluate whole-body mechanical efficiency (ME) in a large group of chronic obstructive pulmonary disease (COPD) patients with a wide range of degrees of illness and (2) to examine how ME in COPD is related to absolute work rate and indices of disease severity during exercise testing. METHODS: A total of 569 patients (301 male patients; GOLD stage I: 28, GOLD stage II: 166, GOLD stage III: 265, and GOLD stage IV: 110) with chronic obstructive pulmonary disease (COPD) were included in the data analysis. Individual maximal workload (watt), peak minute ventilation ( E, L/min body temperature and pressure, saturated), and peak oxygen uptake ( O2, mL/min standard temperature and pressure, dry) were determined from a maximal incremental cycle ergometer test. Ventilatory and metabolic response parameters were collected during a constant work rate test at 75% of the individual maximal workload. From the exercise responses of the constant work rate test, the gross ME was calculated. RESULTS: The mean whole-body gross ME was 11.0 ± 3.5% at 75% peak power. The ME declined significantly ( P < .001) with increasing severity of the disease when measured at the same relative power. Log-transformed absolute work rate ( r = .87, P < .001) was the strongest independent predictor of gross ME. Body mass was the single other variable that contributed significantly to the linear regression model. CONCLUSIONS: Gross ME in COPD was largely predicted by the absolute work rate ( r = .87; P < .001) while indices of the severity of the disease did not predict ME in COPD. Abstract : It has been suggested that diminished mechanical efficiency (ME) exacerbates the clinical impact of COPD. From constant work rate cycle ergometer data in 569 patients, it was concluded that ME in COPD is largely predicted by the absolute work rate while the severity of the disease did not predict ME.